Reformasi Tata Negara dan Pengaruhnya terhadap Perlindungan Hak - hak Kewarganegaraan di Indonesia - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Zhelika Wahyu Wardhani; Jovita Dwi Kusumastuti; M. Adil Hakim Al Hadi (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2024)
Indonesia's constitutional reform since 1998 has brought significant changes to the governance system, legal framework, and the protection of civil rights. This study analyzes the impact of the reform on civil rights protection, focusing on the legal and policy dynamics in the post-reform period. Key changes include the amendments to the 1945 Constitution, decentralization of power, and the strengthening of state institutions such as the Constitutional Court. While the legal framework for human rights has been reinforced, challenges persist, including the harmonization of regional and national regulations and corruption, which undermines public access to basic rights such as healthcare, education, and justice. Decentralization often produces discriminatory policies against religious, ethnic, and sexual minorities, while past human rights violations and identity politics exacerbate social tensions. This study employs a normative method with historical and juridical approaches. To enhance civil rights protection, improved oversight of regional regulations, the abolition of discriminatory policies, anti-corruption measures, and transitional justice mechanisms for addressing past human rights violations are essential. Strengthening civil society and judicial reform are also critical steps toward achieving more effective and equitable civil rights protection.